Application of CORE Learning to Improve Mathematical Connection Capabilities and Self-Efficacy - Eka Yanuar Ramadhani; Anggun Badu Kusuma (MEJ (Mathematics Education Journal), 2020)
The study aimed to improve the skills of students mathematical connections and self-efficacy for grade VII D of SMP N 3 Sidareja in the 2018/2019 academic year through CORE (Connecting, Organizing, Reflecting, and Extending) learning on the topic of triangles and rectangles. The study was conducted in three cycles and each cycle consisted of planning, action, observation, evaluation, and reflection stages. The instrument used was a description test to measure the skills of students' mathematical connections given at the end of each cycle, while the instrument used to measure self-efficacy was self-efficacy questionnaire. Based on the findings, each cycle obtained an improvement. The first cycle obtained mathematical connection skills by an average of 64.74, 77.24 in the second cycle, and 81.41 in the third cycle. The average results of students self-efficacy in grade VII D in the first the cycle was 69.67, 76.05 in the second cycle, and 79.85 in the third cycle. Based on the data above, it can be drawn that there was an improvement of students' mathematical connection skills and self-efficacy from cycle I to cycle II and from cycle II to cycle III through CORE learning (Connecting, Organizing, Reflecting, and Extending).